Replica Bit-Line Technique for Internal Refresh in Logic-Compatible Gain-Cell Embedded DRAM. (July 2020) - Harel, Odem; Nachum, Yarden; Giterman, Robert
Abstract: Embedded memories, mostly implemented with static random access memory (SRAM), dominate the area and power of integrated circuits. Gain-cell embedded DRAM (GC-eDRAM) is an alternative to SRAM due to its high density, low power consumption, and two-ported functionality. However, GC-eDRAM requires periodic refresh cycles to maintain its data due to its dynamic storage mechanism. The refresh operation is typically handled at a memory controller level, resulting in an energy overhead and limited memory availability. In this paper, we propose a new approach for the realization of the refresh operation using an internal refresh mechanism, which supports an efficient row-wise refresh operation within a single clock cycle, providing 100% write access availability at a reduced refresh latency and power. An 8 kbit GC-eDRAM array with integrated internal refresh and replica bit-line was implemented, demonstrating up-to 30% reduced refresh latency and 65% reduced read energy at a low cost of 2.4% array area overhead, compared to a conventional GC-eDRAM array without internal refresh capabilities.